2014
DOI: 10.3389/fpubh.2014.00138
|View full text |Cite
|
Sign up to set email alerts
|

Terror Medicine as Part of the Medical School Curriculum

Abstract: Terror medicine, a field related to emergency and disaster medicine, focuses on medical issues ranging from preparedness to psychological manifestations specifically associated with terrorist attacks. Calls to teach aspects of the subject in American medical schools surged after the 2001 jetliner and anthrax attacks. Although the threat of terrorism persists, terror medicine is still addressed erratically if at all in most medical schools. This paper suggests a template for incorporating the subject throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The course introduces fourth year students to the field of Terror Medicine and its relationship to Emergency and Disaster Medicine. It explores medical features distinctively associated with terrorism events in four broad areas: preparedness, incident management, nature of injuries, and psychological issues 4 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The course introduces fourth year students to the field of Terror Medicine and its relationship to Emergency and Disaster Medicine. It explores medical features distinctively associated with terrorism events in four broad areas: preparedness, incident management, nature of injuries, and psychological issues 4 …”
Section: Methodsmentioning
confidence: 99%
“…The elective is part of a plan to broaden familiarity and develop competency in the subject throughout the medical school curriculum. 3 This study provides an overview of the course over three iterations and reactions to it by participants.…”
Section: Introductionmentioning
confidence: 99%
“…When asked to identify a suitable format to teach and enhance disaster medicine education, elective coursework was preferred by 88% of the medical schools, while only 56% were in favor of establishing it as its own field of study and teaching. However, it has been shown that while electives are highly accepted by students, electives are only able to reach a few students and can therefore only be a temporary remedy [ 25 ], [ 32 ], [ 33 ]. This rather cautious attitude towards engagement in enhancing disaster medicine teaching may also be explained from the responses that most medical schools expected financial and administrative obstacles when expanding disaster medicine teaching.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the number of victims is of a massive character. These "unique injuries" are connected with terrorism creating substantial difficulties for the existing systems to give emergency medical aid, both from the point of view of organization and provision of aid [9][10][11]. The factors complicating the work of emergency medical aid system and influencing on the quality of giving aid to the injured people are: time delay of pre-admission stage, specificity of the obtained injuries, an unpredictable course of associated traumas, considering the character of the applied damaging factor, and inadequately trained medical staff.…”
Section: Introductionmentioning
confidence: 99%